(untitled) (Al-Qamar, 2022)
Nullification has much importance to resolve contradiction of Ḥadiths. There are different opinions of the jurists about the conditions of Nullification. This research article aims to discuss different views of jurists about it particularly in the light views of an early theologian Al-Ṭaḥāwī. After defining the term Nullification in its meanings، forms and conditions have been described and analyzed. Analytical method of research has been adopted to conduct the research. It can be concluded that al-Ṭaḥāwī agrees in most of the conditions of abrogation to the jurists but he has different point of view about more power of abrogating order over abrogated. He is in favour of equality of both abrogating and abrogated orders.